Can pregnancy-associated plasma protein-A be a marker for the assessment of atherosclerosis risk in patients with chronic plaque psoriasis? - Polat, Mualla; Bugdayci, Guler; Sahin, Asli; Kaya, Hatice; Sezer, Tuna; Ozturk, Serkan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is an immune-mediated chronic inflammatory dermatosis. Several studies have shown that patients with psoriasis have a much greater risk of cardiovascular diseases than the normal population. The chronic inflammation observed in psoriasis is thought to have a role in the development of atherosclerosis and vascular endothelial injury. Aim: To examine serum pregnancy-associated plasma protein-A (PAPP-A) levels, which has been regarded as a marker of early stage atherosclerosis in patients with psoriasis that do not have concurrent conventional cardiovascular risk markers. Material and methods : Forty-one patients diagnosed with a chronic plaque type of psoriasis and 42 equally matched healthy volunteers were included in this study. The PAPP-A levels were compared between patient and control groups and the association between PAPP-A levels and disease duration and severity were evaluated in the patient group. Results: Statistically, serum PAPP-A levels were significantly higher in the psoriasis group than in the control group (p = 0.015). Serum PAPP-A levels were found to be positively correlated with severity (p = 0.036, r = 0.329) and duration (p = 0.014, r = 0.269) of the disease. Conclusions : As a marker of early stage atherosclerosis, PAPP-A levels were elevated in the psoriasis group and were correlated with disease duration and severity. This elevation reveals the presence of atherosclerosis in patients with psoriasis. Further studies are needed to confirm the use of PAPP-A as an available and inexpensive screening test and cardiovascular risk assessment for all centers.